2017
DOI: 10.1111/all.13256
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects: Galectin‐1 and specific immunotherapy for allergic responses in the intestine

Abstract: Long-term effects of specific immunotherapy on intestinal allergy can be achieved with Gal-1/SIT therapy by inhibiting mast cell activation and facilitating Treg development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…In a murine model of oral allergy syndrome, administration of Gal-1 suppressed allergic reaction induced by food allergens by inhibiting IL-4 production, recruitment of mast cells and eosinophils, and synthesis of histamine (41). More recently, Gal-1 has been shown to synergize with allergen-specific immunotherapy, providing long-term benefits in animal models by targeting mast cells and facilitating Treg development (122). Overall, these reports suggest that Gal-1 influences the resolution of allergic reactions and might represent a useful tool for the treatment of allergic diseases.…”
Section: Gal-1 As a Tuner Of Allergic Inflammation And Asthmamentioning
confidence: 99%
“…In a murine model of oral allergy syndrome, administration of Gal-1 suppressed allergic reaction induced by food allergens by inhibiting IL-4 production, recruitment of mast cells and eosinophils, and synthesis of histamine (41). More recently, Gal-1 has been shown to synergize with allergen-specific immunotherapy, providing long-term benefits in animal models by targeting mast cells and facilitating Treg development (122). Overall, these reports suggest that Gal-1 influences the resolution of allergic reactions and might represent a useful tool for the treatment of allergic diseases.…”
Section: Gal-1 As a Tuner Of Allergic Inflammation And Asthmamentioning
confidence: 99%
“…In addition, rGal-1 did not reduce plasma IgE levels 24 hours after the last OVA challenge in an OVA-induced atopic dermatitis mouse model [13]. However, another line of research related to long-term treatment with rGal-1 and allergen-specific immunotherapy found that rGal-1 markedly decreased the plasma IgE levels in an OVA-induced intestinal allergy mouse model [35]. These differences may suggest that downregulation of IgE by rGal-1 in allergic inflammation was time-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Following our established procedures, an FA mouse model was developed. Briefly, mice were firstly sensitized by subcutaneous injection of 20 μg CT/100 μg OVA at days 1 and 3 of week 0, and then, from week 1 to week 4 mice were gavage‐fed with OVA (1 mg/mouse) and cholera toxin (20 μg/mouse) in 0.1 mL saline once a week.…”
Section: Methodsmentioning
confidence: 99%
“…Food allergy mice were orally challenged with 50 mg OVA/mouse on week 5 and sacrificed next day. The FA relevant response was assessed with our established procedures, including diarrhoea and core temperature, serum levels of specific IgE and mouse mast cell protease‐1 (mMCP1), levels of Th2 cytokines in the intestinal tissue protein extracts and the intestinal epithelial barrier permeability (see below). The experimental procedures can be referred to our publication …”
Section: Methodsmentioning
confidence: 99%